Transformasi Pendidikan: Konstruktivisme Dalam Konteks Kurikulum Merdeka Untuk Membentuk Pelajar Pancasila Yang Berkarakter - Diyah Nadiyah; Syansuri Abdurahman, Indra; Hidayat, Sholeh (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2024)
This research aims to describe the Merdeka Curriculum designed by the Ministry of Education and Culture to form students who have the character of Pancasila values ​​related to the philosophy of constructivism through the Merdeka Belajar program. This research applies qualitative research using the literature study method. The object of this research is an article that discusses constructivism in the context of an independent curriculum to form Pancasila students with character. Data collection was carried out by looking for sources from books and journal articles that were appropriate to the research. Data analysis uses content analysis techniques starting from analyzing research results and taking notes. The results of this research are that the independent curriculum is in accordance with the philosophy of constructivism which not only receives information, but students are active and able to develop their potential in accordance with the values ​​of Pancasila